Sand chronicles. Vol. 01 - Ashihara, Hinako (Viz Media, 2008)
After her parents' divorce, Ann moves to Shimane with her mother. At first Ann doesn't like living in the country, but then she meets Daigo and other kids her age and finds a place for herself.